Influencing Factors on the Physicochemical Characteristics of Tea Polysaccharides - Hu, Ting (Molecules, 2021)
Tea polysaccharides (TPSs) are one of the main bioactive constituents of tea with various biological activities such as hypoglycemic effect, antioxidant, antitumor, and immunomodulatory. The bioactivities of TPSs are directly associated with their structures such as chemical composition, molecular weight, glycosidic linkages, and conformation among others. To study the relationship between the structures of TPSs and their bioactivities, it is essential to elucidate the structure of TPSs, particularly the fine structures. Due to the vast variation nature of monosaccharide units and their connections, the structure of TPSs is extremely complex, which is also affected by several major factors including tea species, processing technologies of tea and isolation methods of TPSs. As a result of the complexity, there are few studies on their fine structures and chain conformation. In the present review, we aim to provide a detailed summary of the multiple factors influencing the characteristics of TPS chemical structures such as variations of tea species, degree of fermentation, and preparation methods among others as well as their applications. The main aspects of understanding the structural difference of TPSs and influencing factors are to assist the study of the structure and bioactivity relationship and ultimately, to control the production of the targeted TPSs with the most desired biological activity.